Strengthening the Love of Reading Character by Using an Electronic Module Based on Local Wisdom - Asrial, Asrial; Syahrial, Syahrial; Kurniawan, Dwi Agus; Luthfiah, Qonita (Universitas Pendidikan Ganesha, 2022)
Reading is an important skill that students must master because it helps students expand their knowledge, communicate with others, and continue their education. This study aims to analyze the relationship between indicators of reading love character which is integrated with e-module based on local wisdom of Pangkalan Babu mangrove ecotourism. The research method uses associative quantitative research, namely connecting an indicator. The sample of this research is class IV students, totalling 22 people, with a purposive sampling technique. The data collection instrument used was a reading interest questionnaire and a reading interest questionnaire. The questionnaire was the result of a research questionnaire. It is said to be valid if the statement in the research questionnaire can reveal something to be measured. Data analysis used descriptive, inferential statistics, namely analyzing data by describing the data collected. This research shows that the students' reading fondness character has a good category, seen from the indicators of reading love character after using local wisdom-based e-modules, strengthened by the correlation results obtained by 0.720 and produces a positive relationship. So, teachers need to implement e-modules based on local wisdom to instil students' reading love character.